Sinus histiocytosis (Rosai- Dorfman disease) presenting with solitary cutaneous nodule: a very rare clinical entity - Emilia Duarte-Williamson; Fiona Antony; Radu Rotarescu (Mattioli1885, 2012)
Sinus histiocytosis is a rare inflammatory disease mainly affecting the cervical lymph nodes, presenting with skin lesions in 10% of cases. Our patient had a solitary nodule on the trunk without any other clinical signs. The histology reported a dermal neoplasm composed mainly of macrophages and lymphocytes. Macrophages were aggregated in clusters resembling lymph node sinuses. Lymphophagocytosis or emperipolesis (the presence of an intact cell within the cytoplasm of another cell) was noted and the diagnosis of sinus histiocytosis established.